Dietary and immunonutrient intake to improve nutritional status and immunity during the COVID-19 pandemic (Research, Society and Development, 2023)
With the emergence of the new Coronavirus in 2019 and the rapid advance of the virus in a few months, the whole world was oppressed by the biggest pandemic of the 21st century. In this way, the present study aims to present nutritional recommendations to improve immunity and prevent COVID-19 diseases. The study is a systematic review, the bibliographic survey was carried out from October 2021 to April 2022. The following descriptors available in the DeCS Health Sciences descriptors were used: COVID-19, Sars Cov-2, Nutrition , Antioxidant and Immunonutrients. The Boolean operators AND and OR were used, performing different combinations/crosses in the databases. Inclusion criteria: Full online articles, cross-sectional, descriptive, quantitative, qualitative, observational, exploratory and review, in English, Spanish and Portuguese. Exclusion criteria: experience reports and case studies. As a result, it was observed that among the most relevant micronutrients during the COVID-19 pandemic were vitamin C and D, in addition to selenium, zinc, magnesium in addition to prebiotic foods, probiotics, B vitamins and omega 3. It is concluded that when administered in a healthy way, nutrients can act in strengthening the body due to the maintenance of the immune response.